589 Reducing Single-Use Surgical Instruments During Laparoscopic Appendicectomy: Using Sustainable Quality Improvement as a Catalyst to Encourage Wider Behavioural Change in a Surgical Department. (19th August 2022) - Ford, Bryony; Labib, Peter; Kanwar, Aditya; Sanders, Grant; Douie, Walter; Winfield, Michelle
Abstract: Aim: Consumables are responsible for 32% of surgery associated CO2 emissions after excluding anaesthetic gases. We aimed to reduce the carbon footprint of laparoscopic appendicectomies by addressing equipment issues whilst also meeting the triple bottom line of financial, environmental, and social impacts. Method: In a single-centre, a questionnaire was distributed to establish the frequency of, and reasons for, single-use instrument use. A separate questionnaire identified areas for improvement within existing appendicectomy sets. An evaluation of 25 appendicectomies was undertaken, documenting single-use instrument usage. New appendicectomy sets were developed, including additional reusable instruments, and procuring new ports, trialling these in subsequent appendicectomies. Financial impact was calculated based on current procurement prices. Environmental impact was calculated by carbon costing the production, transport and disposal of consumables using published emission factors. Social impact was assessed using staff surveys. Results: 110 single-use instruments were opened in 25 appendicectomies. Our trust performs ∼500 appendicectomies/year, therefore equating to ∼2180 instruments/year that could be avoided by using reusable alternatives. Based on an estimated 75% reduction in consumables, the new set saves £34, 423 and 512kg CO2e per year over the predicted seven-year life span of the instruments. Based on existing practice, the capital investment required for new instruments (£19, 731) will pay for itself within six months. Reduced consumable reliance decreases the volume of waste being incinerated, tackling scope one emissions and local air pollution. Conclusions: These results demonstrate that sustainable changes can be cost saving and reduce carbon emissions. This approach has translational potential across all surgical specialities using single-use instruments.